The Implementation of State Policy of Power Cleaning in the Conditions of Political Transformation: Experience of Ukraine and Countries of Central and Eastern Europe - Goshovska, Valentyna; Goshovskyi, Volodymyr; Dubchak, Liudmyla (European Journal of Sustainable Development, 2020)
The article analyzes the problems of realization of the state policy of power cleaning in the countries of Central-Eastern Europe (Poland, Czech Republic, Hungary, Baltic countries), and in particular in Ukraine. It has been found that in various countries this step in the public administration was taken since the fall of the communist regime. However, everywhere it was carried out by its own rules. The attention is drawn to the fact that the power cleaning through lustration should be ensured in the light of a wide range of threats that pertain to the human rights sphere and the principle of the presumption of innocence. This was relevant for every state that embarked on the path of transformational change to the implementation of a state policy of power cleaning. None of the countries that have taken such a political step in the public administration system went this route easily (there were both claims to the laws with subsequent legislative initiatives to amend them, and suits to courts of various instances to restore human and citizen’s rights and freedoms). However, there were also positive consequences, which resulted in the cleaning of the authorities of the respective countries from the influences of interested pro-communist political forces, which hindered democratic transformations in the states. Regarding the characteristics of the state policy of power cleaning by lustration in Ukraine, which began only in 2014, we drew attention to the fact that it had a different meaning: it was not aimed at combating the communist past, but at overthrowing the current political regime of “Yanukovych times”. There were some problems, which reflected the emergence of relevant issues in such events of the public administration system, which caused criticism from a number of external international human rights organizations (for example, the Venice Commission), and led to massive claims to courts of various instances aimed to restore of claimants' rights. Also the article draws attention to the fact that lustration, as a mechanism of power cleaning, is an appropriate political step on the way to democratization of society and overcoming the negative consequences of the activity of undemocratic political regimes. However, its implementation requires a prudent approach to defining the principles of legal regulation, the establishment of appropriate institutions to ensure the implementation of lustration and guaranteeing the protection of human and citizen's rights and freedoms from political persecution. Keywords: sustainable development, public policy, cleaning of power, lustration, protection of human and citizen's rights and freedoms.